O11.7. INVESTIGATING THE STRUCTURAL CORRELATES OF APATHY WITHIN THE PSYCHOSIS CONTINUUM. (9th April 2019) - Kirschner, Matthias; Burrer, Achim; Yau, Yvonne; Abbasi, Nooshin; Habermeyer, Benedikt; Maatz, Anke; Seifritz, Erich; Dagher, Alain; Kaiser, Stefan
Abstract: Background: Apathy is one of the most severe and debilitating symptoms in schizophrenia. Evidence suggests that motivational deficits are associated with striatal and orbitofrontal structural abnormalities. However, it is unclear whether this holds across subclinical and early stages of the psychosis spectrum. Here, we investigated whether motivational deficit in healthy individuals with schizotypal personality traits (SPT) and patients with first episode psychosis (FEP) are associated with reduced striatal volume and reduced thickness of the orbitofrontal cortex (OFC). Methods: We analyzed T1-weighted brain images from 27 healthy individuals with high schizotypal personality traits, 26 patients with FEP and 28 controls using Freesurfer (http://surfer.nmr.mgh.harvard.edu/ ). We evaluated volumes of the nucleus accumbens, putamen, caudate and cortical thickness of the OFC, as well as apathy and diminished expressivity from the Brief Negative Symptom Scale. Results: In individuals with SPT apathy was negatively associated with lower volume of right nucleus accumbens (r=-.548, p=.007), and right and left putamen (right: r=-.58, p=.003: left: r=-.63, p=.001) accounting for age, gender and intracranial volume. In patients with FEP, apathy was negatively associated with reduced OFC thickness (r=-.644, p=0.001) accounting for age, gender and global cortical thickness. None of the structural abnormalities were associated with diminished expressivity. On a group level, we found a significant effect of group in the right OFC (F(2, 76)=5.1, p=.009) and left OFC (F(2, 76)=5.8, p=.005) with reduced OFC thickness in patients with FEP compared to individuals with SPT (right: p=.005, left: p=.011) and controls (right: p=.035, left: p=.04). Discussion: Our findings suggest that structural correlates of apathy can already be observed in non-clinical unmedicated populations and early stages of psychosis. These distinct structural correlates of apathy may help to identify symptom specific subgroups within the psychosis continuum and foster progress to develop individualized treatments.